Novel Tumour Suppressor Genes Implicated In Oral Cancer - S, MADHUMITHAA; J, VIJAYASHREE PRIYADHARSINI; EZHILARASAN, DEVARAJ (The journal of contemporary issues in business and government, 2021)
The cancer of oral cavity is the most prevalent with a recorded incidence rate higher in male than in females. In India, oral and nasopharyngeal carcinomas comprise upto half of all malignancies. The influence of carcinogens and region specific epidemiological factors like tobacco, betel leaf and quid chiming, makes it more aggressive and resistant to treatment. Tumour suppressor genes (TSG's) are genes that prevent cells from acquiring malignant characteristics. The aim of this study is to give a brief review on the novel tumour suppressor genes implicated in oral cancer in the last decade. A review with recent information about tumour suppressor genes in association with oral cancer and its role was derived from various sources such as Medline, Google scholar, MESH, Cochrane etc. Novel genes and signalling pathways have been implicated in the process of tumorigenesis in the last few years. The reports and studies discussed in this review would help in gaining knowledge about the role of tumor suppressor genes in oral cancer. A more comprehensive knowledge on the pathways will enable us to choose candidate genes as targets of therapy.